2020
DOI: 10.21608/mjvh.2020.80662
|View full text |Cite
|
Sign up to set email alerts
|

The role of endoscopic ultrasound in patients with choledocholithiasis: A pilot study

Abstract: Background and study aim. Endoscopic ultrasound (EUS) is a diagnostic modality that continues to expand its clinical applications. The aim of this study is to evaluate the diagnostic role of EUS in common bile duct stones. Patients and methods: This study was carried on 29 patients with suspected CBD stones from them only 15 patients were diagnosed as Common Bile Duct stone(s). Endoscopic retrograde cholangiopancreatography (ERCP) is considered as gold standard for diagnosis of CBD stones and compare EUS findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This result is in the same line of study number (26) that found that the two approaches were statistically equivalent as demonstrated by the McNemar conditional 1-sided test for equivalence of sensitivities (P = .27) in their comparison of Primary upper endoscopy (EGD) and transabdominal US (TUS). (26) Also, study number (21) .reported that, there are no statistically significant differences were found between EUS and MRCP in the diagnosis of CBD stones, but a trend toward higher sensitivity and specificity for EUS compared to MRCP was evident. (21) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This result is in the same line of study number (26) that found that the two approaches were statistically equivalent as demonstrated by the McNemar conditional 1-sided test for equivalence of sensitivities (P = .27) in their comparison of Primary upper endoscopy (EGD) and transabdominal US (TUS). (26) Also, study number (21) .reported that, there are no statistically significant differences were found between EUS and MRCP in the diagnosis of CBD stones, but a trend toward higher sensitivity and specificity for EUS compared to MRCP was evident. (21) .…”
Section: Discussionmentioning
confidence: 99%
“…(26) Also, study number (21) .reported that, there are no statistically significant differences were found between EUS and MRCP in the diagnosis of CBD stones, but a trend toward higher sensitivity and specificity for EUS compared to MRCP was evident. (21) . Study number concluded that, EUS is a very useful technique for the indication of cholecystectomy in patients with microlithiasis sludge and typical symptoms of biliary colic (27) while, study (28) .concluded that, EUS seems to be a promising imaging method in the detection of microlithiasis in the gallbladder in patients with clear biliary colic and normal transabdominal US (28) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alhawarey et al [22] demonstrated that EUS, as diagnostic tool, has sensitivity, specificity, PPV, NPV, and accuracy of 100%, 92.8%, 93.7%, 100%, and 96.5% respectively.…”
Section: Discussionmentioning
confidence: 99%